Olympic Messages: Olympic Ideology and Olympic Social Reality - Patsantaras, Nikolaos (CHOREGIA- Scientific Forum in Sport Management, 2008)
Olympic sports constitute an exceptionally complex and multidimensional social space, particularly in the framework of accelerated social transformations. The social meaning of Olympic communication has radically been transformed, principally during the last two decades. The influences of other social spaces such as the economy, the mass media and politics have lead to a notional heterogeneia of modern Olympic sports semantics. Today, Olympic institutions and organizational configurations direct their interests exclusively towards economic structures. In other words, implemented without reservations are all the processes that support the commercial profile of Olympic sports and promote it as a commercial-entertainment spectacle. As a result serious contradictions and inconsistencies arise between today’s Olympic social reality and the values advocated by the Olympic movement and the Olympic Charter. Olympic communication practices are primarily connected to economic interests, and as a result it is difficult to define them as conveyors and as means of reflection for foundational social and ethical values. Consequently, the original messages advocated by the 19th century Olympic movement– and in particular by Coubertin with regard to Olympism and Olympic Education– are not reproduced and reactivated in today’s Olympic social reality. Inevitably questions arise such as (1) What is the meaning of Olympic ideology, Olympism and Olympic Education? (2) Is there a discrepancy or a lack of correspondence between the social and ethical values advocated by the Olympic movement and Olympic social reality?